Determinants of High-Risk Pregnancy: A Systematic Literature Review - Ni Gusti Made Ayu Agung Budhi; Mardeyanti Mardeyanti; Jumiati Jumiati; Sri Sukamti; Karningsih Karningsih; Yulia Fauziah Amizuar (International Forum of Researchers and Lecturers, 2025)
Pregnancy, labor, and the postpartum period can all be more hazardous for the health of the mother and fetus in high-risk pregnancies. By doing a thorough literature analysis, this study seeks to determine the contributing factors to high-risk pregnancies. Methods: A systematic review of the literature utilizing ten national journals from PubMed and ten foreign journals from Google Scholar. The inclusion criteria were observational and cohort research articles published between 2020 and 2024, as well as systematic reviews of research articles with their determinants found in databases like PubMed and Google Scholar. Maternal factors (age <20 or >35 years, history of chronic diseases, and maternal health condition), obstetric factors (pregnancy spacing too close, multiparity, or history of previous pregnancy complications), and socioeconomic factors (low education, limited access to health services, and poor economic status) are the factors that contribute to high-risk pregnancies, according to the analysis. Furthermore, bad lifestyle choices like drinking alcohol, smoking, and not eating enough food all play a big part. The study's findings emphasize the value of multifaceted initiatives that include education, better access to healthcare, and a comprehensive approach to policy in order to lower high pregnancy risk.